The human myocardium harbors a population of naive B-cells with a distinctive gene expression signature conserved across species - Bermea, Kevin C.; Kostelecky, Nicolas; Rousseau, Sylvie T.; Lin, Chieh-Yu; Adamo, Luigi (Frontiers in Immunology, 2022)
Introduction Cardiac immunology studies in murine models have identified a sizeable population of myocardial B-cells and have shown that its modulation represents a promising strategy to develop novel therapies for heart failure. However, scarce data on B-cells in the human heart leaves unclear whether findings in rodents are relevant to human biology. Methods We performed immunohistochemical stains to characterize the amount and distribution of B-cells in human hearts, analyzing both fresh and post-mortem tissue. To gain insight into the biology of human myocardial B-cells we analyzed publicly-available spatial transcriptomics and single-cell sequencing datasets of myocardial and peripheral blood mononuclear cells (PBMCs). We validated these findings on primary B-cells sorted from the heart and peripheral blood of left ventricular assistive device recipients. To identify biological pathways upregulated in myocardial B-cells across species, we compared differential gene expression in myocardial vs peripheral blood B-cells across the studied human datasets and published rodent datasets. Results In healthy human heart samples, we found B-cells at a ratio of 1:8 compared to T-cells (2.41 ± 0.45 vs 19.36 ± 4.43, p-value <0.001). Myocardial B-cells were more abundant in the interstitium compared with the intravascular space (p-value=0.011), and also more abundant in the myocardium vs. epicardium (p-value=0.048). Single-cell gene expression analysis showed that the human myocardium harbored mostly naive B-cells with a gene expression profile distinct from that of PBMC B-cells. Cross-comparison of differentially-expressed genes in myocardial vs. PBMC B-cells across human and rodent datasets identified 703 genes with consistent differential gene expression across species (binomial p-value=2.9e-48). KEGG pathway analysis highlighted “B-cell receptor signaling pathway,” “Antigen processing and presentation,” and “Cytokine-cytokine receptor interaction” among the top pathways upregulated in cardiac B-cells (FDR <0.001) conserved between species. Conclusions Like the murine heart, the human heart harbors naive B-cells that are both intravascular and extravascular. Human myocardial B-cells are fewer and more evenly distributed between these two compartments than rodent myocardial B-cells. However, analysis of single-gene expression data indicates that the biological function of myocardial B-cells is conserved across species.